Smart Banjar Concept Development: A Qualitative Research - I Dewa Made Adi Baskara Joni; Bazilah A. Talip; Shamsul Anuar Mokhtar; I Putu Hendika Permana (Jurnal Krisnadana, 2026)
The village and Banjar administrations manage cultural, religious, and socioeconomic activities in Bali. As a result of its customs and heritage, Bali has grown to be a world-famous tourist destination with substantial economic consequences. The influence of Villages and Banjar on tourism growth must benefit the community. The Banjar function must be strengthened to maintain the community's economic resilience by involving financial institutions such as Micro Finance. The synergy between Banjar and Micro Finance can support the development of Micro Enterprises, thereby impacting people's welfare. Based on this, the concept of the Smart Banjar was developed. To conduct qualitative research, interviews were conducted with the Leader of the Village, the Leader of the Banjar, the Leader of Micro Finance, and the Micro Enterprise. The analysis process produces four network diagrams: Micro Enterprise, Micro Finance, Information and Communication Technology Adoption, and Smart Concept. Based on the research results, Banjar, as a community entity, is part of the village-centered program. One existing program is the digitization of Micro Enterprises. It can be done by developing a smart concept that involves community-based Micro Finance. With Micro Finance's involvement as an optimal community-based economy, it can achieve community welfare.